Karakteristik fisikokimia penyedap rasa nabati hidrolisat tempe gembus dan jamur tiram menggunakan foam-mat drying - Yesy Dwita Arvialika; Rahmah Utami Budiandari; Rima Azara (University of Insan Cendekia Mandiri, 2026)
This study aimed to determine the effect of the proportion of tempe gembus and oyster mushroom on the physicochemical characteristics of a plant-based flavor enhancer produced by foam-mat drying. The study employed a single-factor Completely Randomized Design (CRD) with seven treatments: T1 (100:0), T2 (70:30), T3 (60:40), T4 (50:50), T5 (40:60), T6 (30:70), and T7 (0:100). The results showed that the proportion of tempe gembus and oyster mushroom significantly affected the water solubility index, color profile, glutamate content, and ash content of the plant-based flavor enhancer. Based on the effectiveness index analysis, the best treatment was T1 (100% tempe gembus), with the following characteristics: glutamate content of 19.47 mg/g, moisture content of 7.39%, ash content of 0.95%, water solubility index of 0.0933 g/mL, yield of 17.66%, and color profile (L: 79.02; a*: 3.45; and b*: 16.45).